Michele Sorice, Partecipazione democratica. Teorie e problemi [Democratic Participation. Theories and Problems], Mondadori, Milano, 2019, ISBN 978-88-6184-706-4, pp. 162. - Andrea Grippo (Coordinamento SIBA, 2020)
For Book Reviews abstract is not required